A phylogeny of Emilia (Senecioneae, Asteraceae) – implicationsfor generic and sectional circumscription - Mapaya, Ruvimbo J.; Cron, Glynis V. (Taxon, 2021)
Emilia is a widely distributed, mainly African, palaeotropical genus in the tribe Senecioneae (Asteraceae). It comprises117 species, most of which are annual herbs. Bayesian and parsimony phylogenetic analyses were performed on 51 Emilia speciesalong with closely related genera in the Senecioneae using nuclear ITS and plastid trnL-trnF sequence data to address questions aroundthe generic circumscription of Emilia, including the status of the similar genera Emiliella and Bafutia, assess Jeffrey’s sectional classi-fication of Emilia, and evaluate the distinctness of the morphologically similar species in the large-headed Emilia coccinea complex.Both nuclear and plastid phylogenies reveal Emilia to be paraphyletic and polyphyletic, with Bafutia and Emiliella nested withinEmilia, and Jeffrey’s sectional classification is not supported. The phylogenies provide additional evidence that Emilia coccinea andE. caespitosa should be synonymised, as shown by published phenetic cluster and multivariate analyses. The necessary taxonomicchanges are made in this manuscript.